Clostridioides difficile Induced Rhabdomyolysis Associated With Decompensated Cirrhosis. (December 2022) - Dungan, William; Young, Gabrielle; Collins, Bradley; Romano, John; Honko, Nicholas; Rockey, Don
Rhabdomyolysis (RBD) occurs secondary to tissue injury, resulting in (muscle) cell lysis and release of intracellular electrolytes and proteins into circulation. An elevation in the muscle enzyme, creatine kinase (CK), is a diagnostic marker and indicates muscle breakdown. Symptoms include dark urine caused by release of myoglobin, myalgias, and acute kidney injury (AKI). RBD is categorized as (1) traumatic, (2) nontraumatic exertional (ie, metabolic myopathies), or (3) non-exertional and non-traumatic. Clostridioides difficile (CD) has been previously reported to cause RBD, but the risk factors, pathogenesis, and recommended treatment regimen remain unclear.